Textile wastewater treatment by anaerobic sludge blanket reactor (Bangladesh Journal of Scientific and Industrial Research, 2020)
In this study, performance of a lab-scale hybrid up-flow anaerobic sludge blanket (HUASB) reactor treating textile wastewater was evaluated under several operating conditions such as i) textile wastewater mixed up with glucose as food, ii) textile wastewater seeded with sewage sludge and glucose and iii) textile wastewater only. In all cases, two days of incubation period was provided for bacterial growth. In the first case, Klebsiella was the primary Species of bacteria growing in the reactor and the removal efficiency of COD and color was 25% and 56.4% respectively. In the second case, Klebsiella and Escherichia coli were the major bacteria and removal efficiency of COD and color was found to be 38% and 65% respectively. In the last case, Pseudomonas bacterium was dominant in the reactor and removal efficiency of COD, BOD and color was 84%, 93%, and 97% respectively. Wastewater treatment without glucose favored the growth of Pseudomonas which has been found to be effective in degrading organics present in textile wastewater. For all cases, reactor performance decreased after the third or fourth cycle of treatment. However, the removal of sludge after the third cycle allowed a high degradation efficiency of organics to be maintained in the reactor. With proper bacterial growth and maintenance, the HUASB reactor can be a huge upgrade from conventional UASB and a suitable alternative to conventional processes for the treatment of textile wastewater.Bangladesh J. Sci. Ind. Res.55(3), 165-172, 2020